Phylogenetic relationship and genotype variation of six Newcastle disease viruses isolated from duck in Indonesia - Naimah Putri; Rahaju Ernawati; Jola Rahmahani; Suwarno Suwarno; Fedik Abdul Rantam (Veterinary World, 2021)
Background and Aim: Newcastle disease viruses (NDVs) are frequently acquired from all ages and types of bird species. In general, ducks are considered as potential reservoirs for different genotypes of NDV and are resistant even to velogenic NDV strains. This research was conducted to genotypically and phylogenetically characterize NDV isolates collected from unvaccinated ducks from Indonesia.